Implementasi Face Detector sebagai Sistem Pengaman Rumah Berbasis Webcam dan Raspberry Pi - Sutarti, Sutarti; Siswanto, Siswanto; Sutardi, Noercholish Madjid (Jurnal Informatika Universitas Pamulang, 2021)
Home security is very important to protect ourselves and our wealth from the crime that is increasingly over the time. CCTV installation is an alternative method to increase home security. The disadvantages of using CCTV are not being able to send notifications to homeowners when foreigners are detected and the lack of supervision from the public and security staff. Therefore, it is necessary to develop a system that can detect the presence of unknown people and provide notifications to homeowners. In this study, implementing a face detector as a home security system using a webcam and a Raspberry Pi. The home security system that is built can recognize the faces of the occupants of the house and can open the door automatically. Face recognition uses the Haar-cascade method which compares images captured by a webcam with a database to recognize the faces of residents of the house. When the system detects the faces of the occupants of the house, the system will drive a servo motor as a door opener. The system also sends notifications via Push-Safer to homeowners when the webcam records an unrecognized face.